SAT0107 BIOMARKERS OF CLINICAL RELAPSE AND RADIOLOGICAL PROGRESSION IN PATIENTS WITH RHEUMATOID ARTHRITISIN REMISSION. OBSERVATIONAL STUDY OF 5 YEARS OF FOLLOW-UP. (June 2019) - Ramirez, Julio; Cuervo, Andrea; Celis, Raquel; Castellanos-Moreira, Raul; Rodriguez-García, Sebastian C.; Ruiz-Esquide, Virginia; Puerta, José Gomez; Sanmartí, Raimón; Cañete, Juan D.
Abstract : Background: Patients with Rheumatoid Arthritis (RA) in remission will present flares during the evolution of the disease.Definitive biomarkers have not been identified to predict flares and radiographic progression (RP) in this kind of patients Objectives: To search biomarkers of clinical relapse and RP in patients with RA in clinical remission Methods: RA patients in clinical remission (DAS28-ESR<2.6 for>6 months) were selected.Clinical, epidemiological and serological data were analyzed.MRI of dominant hand, ultrasound assessment of knees and hands and serum levels of inflammation and angiogenesis biomarkers were evaluated at 0 and 48 weeks.Synovial biopsy was performed in patients with subclinical synovitis.Patients were follow-up for 5 years.Radiological data were collected.Clinical relapse was defined as the loss of remission status involving a therapeutic intervention.RP was defined as the change in the Sharp van der Heijde (SvH) index at 5 years >10.47 [SDD (minimum detectable change)]. Results: 60 patients in DAS28 remission. 1/3 also met remission criteria for SDAI(33.3%), CDAI(31.6%) and ACR(35%).78% were women, mean age 53 years. 82% were ACPA+.26% were taking oral prednisone, 76% DMARDs and 45% biological therapies.48% met criteria for subclinical synovitis(UdAS:SH>2+PD) 1 . After 5 years of follow-up, 44(73%), 11(18%), 9(15%) and 10(17%) patients remained in remission according to DAS28, SDAI, DAI and ACR criteria, respectively. 29 patients (48%) had flares at any time during the 5 years. In the multivariate analysis, the variables that were related to clinical relapse were the BMI (OR 1.6 CI 95% 1.1-2.3), bone edema at baseline (OR 1.2, CI 95% 1-1.5), PD signal at 48w (OR 9.2, CI 95% 1.2-66.7) and the change in levels of CXCL16 (OR 1.04 CI 95% 0.9-1) and ESR (OR 3.6, CI 95% 1.1-12.2) between the first and latest evaluation (Rate). In the subgroup of 23 patients undergoing synovial biopsy, the number of mast cells was higher in those patients (n=10) who flared (p=0.02). 20 patients (33%) changed DMARDs or biological therapy. In the logistic regression analysis, BMI (OR 1.3 CI 95% 1-1.6), biological therapy (OR 17.8 CI 95% 2-167.1), progression of erosions measured by MRI (OR 1.1, CI 95% 1-1.3) and the rate of progression of calprotectin levels during the first year (OR 4.4, CI 95% 1.1-17.2) were the main factors that predicted the change in baseline therapy after 5 years of follow-up. Finally, only 6 patients (10%) had RP according to the SvH index and 7 (12%) had erosion progression.This small number of "progressors" did not allowed more exhaustive analysis of factors predicting RP.However, the number of macrophages and T cells at sinovial tissue (ST) was much higher in patients with RP.Likewise, the first-year rate of bone edema was significantly higher in patients suffering structural progression (p=0.04). Conclusion: 27% of RA patients lost clinical remission (DAS28) after 5 years of follow-up.BMI, baseline bone edema, PD signal at 12m and first-year rate of CXCL16 and VSG levels were predictors of joint flares. Baseline BMI, use of biological therapy, MRI erosions and calprotectin levels predicted the change of baseline therapy for RA. Only 10% of patients had RP along the study.Sinovial mast cells were associated with disease flares. Macrophages and T cells in ST were higher in patients with RP in an exploratory analysis. Reference: [1] Ramirez J, Ruiz-Esquide V, Pomes I, Celis R, Cuervo A, Hernandez MV, et al. Patients with rheumatoid arthritis in clinical remission and ultrasound-defined active synovitis exhibit higher disease activity and increased serum levels of angiogenic biomarkers. Arthritis Res Ther. 2014;16:R5. Disclosure of Interests: Julio Ramirez: None declared, Andrea Cuervo: None declared, Raquel Celis: None declared, Raul Castellanos-Moreira Speakers bureau: MSD, Lilly, Sebastian C Rodriguez-García: None declared, Virginia Ruiz-Esquide: None declared, José Gomez Puerta Speakers bureau: BMS, Pfizer, Amgen, Raimón Sanmartí Speakers bureau: PFIZER, SANOFI, LILLY, MSD, UCB, NOVARTIS, JANSSEN, Juan D. Cañete: None declared